2015
DOI: 10.1108/jfra-06-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and cost stickiness: evidence from Egypt

Abstract: Purpose – This paper aims to examine whether costs respond asymmetrically to demand change, and examine the influence of economic growth on cost stickiness, in the pre- and post-2008 financial crisis periods. Design/methodology/approach – This study uses multiple regression models to investigate the behavior of three costs: selling, general and administrative (SG & A), cost of goods sold (COGS) and operating costs (OCs) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 20 publications
9
56
2
6
Order By: Relevance
“…The estimated value of 2 regression is equal to -0.025%, and -0.092%. Furthermore, Ibrahim [21] agrees with results found that the costs behavior is sticky in prosperity periods, and cost behavior is anti-sticky in recession periods. The estimated value of 2 regression is equal to -0.48%, and 0.20% during prosperity and recession respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The estimated value of 2 regression is equal to -0.025%, and -0.092%. Furthermore, Ibrahim [21] agrees with results found that the costs behavior is sticky in prosperity periods, and cost behavior is anti-sticky in recession periods. The estimated value of 2 regression is equal to -0.48%, and 0.20% during prosperity and recession respectively.…”
Section: Discussionsupporting
confidence: 80%
“…The paper has applied an established methodology to develop the costs and activity relationships [13], [20], managers understand and performance in different situations [11], [21].…”
Section: Models and Soulation Approachesmentioning
confidence: 99%
“…The literature provides empirical evidence that the costs do not always react in a linear way, as suggested by the theory of traditional costs, and the seminal study by Anderson et al, (2003), which showed the sticky cost behavior, known as sticky costs. Such research made emerge new empirical evidence, under which proved the existence of asymmetry in costs, as the findings from studies by Subramaniam and Weidenmier (2003), Calleja et al, (2006), He et al, (2010) Porporato and Werbin (2012), Borgert and , Balakrishnan et al, (2014), Ibrahim (2015) and Pamplona et al, (2016).…”
Section: Introductionmentioning
confidence: 85%
“…Such technique assumes that there is a relation between the costs and organizational activities, so that they are based on the estimate that the costs are changed in accordance with the proportion of changes in activities. Thus, the increase or decrease in activity should provide a symmetrical response in costs, i.e., an increase or decrease to be treated (Ibrahim, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as an extension of our findings, we need to speculate that cost stickiness can be directly and indirectly related to economic growth [64], political uncertainty [65], and credit risk [66]. Managers at internationalizing emerging market firms, particularly Chinese firms, should think over how these factors can be related to their institutional advantages.…”
Section: Theoretical and Managerial/policy Implicationsmentioning
confidence: 73%